Pattern of susceptibility to azoles by E test method in candidemia patients - B., Sri Janani; T., Premamalini; S.V., Rajyoganandh; Kindo, Anupma J. (International Journal of Research in Medical Sciences, 2017)
Background: Blood stream infections due to Candida sp have considerably increased in recent years, along with the increase of drug-resistant isolates in immunocompromised patients. This increase in resistance makes it important to determine the antifungal susceptibility profile of each Candida species isolated from blood prior to treatment. Hence, this study was done to detect the resistant strains of Candida causing candidemia. Methods: About Seventy Candida species isolated from blood cultures were used for this study. These included 27 Candida albicans, 23 Candida tropicalis, 8 Candida parapsilosis, 3 Candida krusei, 2 Candida glabrata and 7 other candida species. Minimum inhibitory concentrations (MIC) of the most commonly used azoles like fluconazole, ketoconazole, itraconazole and voriconazole were determined by E test method. Results: The resistance percentage of Candida albicans for fluconazole and itraconazole was 11.1% and 7.4%; fluconazole resistance in Candida tropicals was 8.7%. Candida parapsilosis had good activity against all azoles with only 12.5% resistance for itraconazole. Conclusions: Fluconazole had good activity against most of the Candida sp except for Candida glabrata and Candida krusei with MIC 90 > 256 µg/ml. Itraconazole was less effective for Candida albicans, Candida glabrata and Candida parapsilosis (MIC 90 >32 µg/ml). Voriconazole was found to be the most effective drug against all species of Candida with low MIC values (MIC 90 < 0.25 µg/ml). Hence it can be used to treat blood stream infections caused by Candida species.